Zen and the art of conquest: a southerly misadventure with Phaedrus and other essays - Moreno, Raul B., author; Sloane, Sarah, advisor; Calderazzo, John, committee member; Kodrich, Kris, committee member (Colorado State University. Libraries, 2011)
As the title suggests, this thesis comprises several works of creative nonfiction. First, "Zen and the Art of Conquest" presents an incomplete narrative, in six chapters, that draws inspiration from Robert Pirsig's Zen and the Art of Motorcycle Maintenance (1974) and other travelogues. In Chapter One, the author embarks on a road trip to Las Vegas that seems haunted by his past--that is, his Peace Corps service in Kyrgyzstan, where "the killing started" just a month ago. Chapter Two begins with a flashback from an earthquake that preceded the killing, but then moves back to the road, where the author has reached Prineville, Oregon, also a stop on Pirsig's journey. Pushing farther south, in Chapter Three, through Indian country, the author recalls childhood memories of Cathlapotle, a Chinook village described in Lewis and Clark's journals. Chapter Four profiles the author's father and grandfather, who devoted themselves to unearthing a Mayan graveyard in Guatemala. The Maya's ancestors migrated south from Asia and then Oregon, the author discovers, and this fact drives his thinking in Chapter Five. He's determined to reach Las Vegas because he wants to put questions about what happened in Kyrgyzstan to a former Peace Corps volunteer living there with his Kyrgyz wife. Chapter Five concludes with the author's arrival in Osh, the scene of the killing, and Chapter Six alternates between his approach to the Oregon-Nevada border and a village feast where Kyrgyz men butcher livestock and grill him about Amerikadan. Three essays constitute the second half of this thesis. "What Happened Yesterday in Baghdad" recounts the author's conversations with a group of Iraqi students visiting Colorado. Their wartime memories resonate with his life as a public radio producer between 2004 and 2008--a time when he assembled reports for correspondents in Baghdad and helped "voice" the words of the conflict's victims. "Exposure Time" reflects on the author's preoccupation with dying in a cycling accident, which in turn offers an entry into recollections of violence in Cartagena, Colombia, and Osh, Kyrgyzstan. The final essay, "I'd Like to Talk About the Bigger Stuff," explores the author's separation from a woman who observes, after his Peace Corps service, that he no longer has compassion for animals. This observation invites a meditation on American relationships with dogs, cats, and wildlife; the roles of dogs, goats, and horses in Kyrgyzstan; and the legacy of the Soviet Union in Central Asia.